The Constantinos Karamanlis Institute for Democracy Yearbook 2009
XI, 113 p.
Keywords: The year 2009 finds Europe at a crossroads. The European Union faces the challenges posed by the Lisbon Treaty under the impact of a major international financial and economic crisis. Transatlantic relations are stimulated by the change of administration in Washington. On both sides of the Atlantic political priorities focus on the build-up of social protection against economic recession, the adoption of innovative energy and environmental policies, the promotion of security and the prevention of humanitarian disasters in unstable areas, notably the Middle East and Africa. This book addresses this complex international environment through essays that were presented in publications and public events of the Constantinos Karamanlis Institute for Democracy. It brings together prominent scholars and policy makers from various national backgrounds. Their contributions highlight policies and ideas that shape issues of international interest, reflecting also the public debate in Greece within the European context.